Multi-criteria analysis for sustainable and cost-effective development of desalination plants in Chile - Sola, Iván; Zarzo, Domingo; Sánchez-Lizaso, José Luis; Sáez, Claudio A. (Frontiers in Marine Science, 2024)
In Chile, there is an increasing demand for freshwater supply for human consumption, agriculture, and industrial activities. In this sense, the country is highly threatened by climate change, which is drastically affecting the availability of water resources in the north-central region due to desertification processes. Therefore, seawater reverse osmosis (SWRO) desalination is becoming one of the most feasible alternatives to address current and future challenges regarding water scarcity in the country. This investigation aims to evaluate potential locations for a sustainable and cost-effective installation of desalination projects; the latter, under a multi-criteria and geographic information system (GIS)-model. The model was tested in the highly water scarcity-threatened Valparaiso Region, Chile, as a case study. The model was developed integrating economic and socio-environmental criteria involved in the development and/or construction of desalination projects. The results of the multi-criteria analysis show that the Valparaıso Region presents optimal areas for developing SWRO projects. Both the northern and central areas of the Region show appropriate locations for installing SWRO plants and their freshwater distribution lines, ensuring short- and long-term water supply, especially for agriculture and population consumption. The results obtained in this study could be extrapolated as a tool to assess the desalination projects development in other world regions to make future desalination projects more viable and sustainable for addressing global water demands.